(untitled) (Journal of Applied Learning and Teaching, 2025)
This study explores the shift from written assignments to synchronous group presentations in a fully online marketing course at a Singapore institution for adult, part-time learners. The change, implemented in mid-2023, aimed to enhance engagement, develop essential skills, and address academic integrity issues arising from AI-generated content. Employing the Community of Inquiry framework which emphasises cognitive, social, and teaching presence, the pilot’s effectiveness was assessed through mixed-method surveys involving both students and instructors. Despite perennial groupwork challenges such as scheduling conflicts and participation issues, the findings indicate that synchronous group presentations enhanced engagement and essential skills development in the digital age. The paper recommends incorporating asynchronous elements and additional support to optimise online group presentations. Although this is a small-scale study, its findings offer valuable insights for educators and institutions striving to enhance learning outcomes and mitigate overreliance on generative AI in assessments.